Identification of novel coding sequences associated with seasonality and water restriction imposition in Eucalyptus grandis by mass spectrometry - Jorge, Gabriel Lemes [UNESP] (2022)
Understanding how plants cope with current climate change and escalating frequency of drought events is crucial for agriculture. Among the plant species of economic importance, Eucalyptus species are widely cultivated for their several industrial applications. However, the current negative effects of changing climate may impose additional challenges on Eucalyptus plant adaptability and development. In this scenario, the study of proteins can provide essential insights into how plants regulate many biological processes under such conditions. Here, we use proteomics, a cutting-edge technology that uses mass spectrometry to identify proteins by correlating known virtual spectra against experimental spectra acquired from large-scale analyses of protein mixtures. We also use a proteogenomics approach that can identify novel peptides not initially predicted by conventional proteomics workflows in the Eucalyptus grandis proteome. First, our goal was to identify and validate novel peptide forms from E. grandis stem samples using a dedicated proteogenomics workflow, which consisted of spectral correlations against modified RNA databases and a de novo peptide sequencing approach. Later, this strategy was applied on a broader scale to identify novel peptide forms in E. grandis leaf samples subjected to the effect of seasonality and water restriction imposition. Known protein and novel peptide identifications provided important insights on how the leaf proteome profile of E. grandis trees changed over different seasons of the year, as well as under water restriction imposition. Those novel peptide identifications, mainly related to the photosynthesis process, decreased the protein stability by altering the quantitative change upon ΔΔG values and non-covalent interactions. Validation of novel identifications was carried out using either Multiple Reaction Monitoring (MRM) or Parallel Reaction Monitoring (PRM) targeted assays that provided further mass spectrometry support for the existence of the novel peptide identifications.